ANALISIS EKSPLORASI DAN VISUALISASI DIVIDEN UNTUK REKOMENDASI INVESTASI PADA SEKTOR PERBANKAN - Puji Lestari; Imam Tahyudin; Retno Waluyo (JURNAL REKAYASA INFORMASI, 2023)
An investment is a binding in a sum of money or other assets that is being made at this time with the hope of obtaining a profit in the future. The banking sector is a financial sector that can be used as an investment option. The most expected profit when someone makes an investment is the acquisition of dividends. Before making an investment, it is important for investors to carry out an analysis of dividend data distributed by bank companies so that investors can find out the picture of the profits they get. In this research, an exploratory analysis and visualization of dividend data were taken from the official dividend record platform which aims to provide bank recommendations that can be used as a place to invest and get maximum profits for investors. The sample was selected using purposive sampling method, 7 bank samples were obtained in this study. The data processing method is carried out using Python tools and visualization using Tableau Desktop. The results obtained from the analysis in this study are recommendations for banks as a place to invest, namely PT. Bank Asia Central Tbk., and PT. Bank Mandiri (Persero) Tbk.